Inhibition of human cytochrome P450 enzymes by licochalcone A, a naturally occurring constituent of licorice. Issue 7 (October 2015) - He, Wei; Wu, Jing-Jing; Ning, Jing; Hou, Jie; Xin, Hong; He, Yu-Qi; Ge, Guang-Bo; Xu, Wei
Highlights Licochalcone A (LCA) could strongly inhibit CYP1A2, 2C19, 2C8, 2C9 and 3A4. LCA caused mixed-type inhibition against CYP1A2, 2C9, 2C19 and 2C8. LCA was a competitive inhibitor towards CYP3A4. The predictions of in vivo herb–drug interactions were performed based on the in vitro data.